2021
DOI: 10.1101/2021.09.29.462391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative genomics uncover mechanisms of renal medullary carcinoma transformation, microenvironment landscape and therapeutic vulnerabilities

Abstract: Renal medullary carcinoma (RMC) is an aggressive desmoplastic tumour driven by bi-allelic loss of SMARCB1, however the cell-of-origin, the oncogenic mechanism and the features of its microenvironment remain poorly understood. Using single-cell and multi-region sequencing of human RMC, we defined transformation of thick ascending limb (TAL) cells into at least three RMC cell states along an epithelial-mesenchymal gradient through a transcriptional switch involving loss of renal transcription factor TFCP2L1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…It has previously been shown that the expression of both genes is upregulated in RMCs [ 5 ], which corroborates our results. Additionally, our findings are in line with the study by Vokshi et al, which showed clusters of cells harboring an EMT signature in single cell transcriptome analyses of a RMC patient sample as well as an enrichment of EMT and hypoxia in two independently generated RMC cell lines [ 13 ]. Although RMCs and ES show similarities in global methylation, as seen in hierarchical clustering ( Figure 1 B), the methylation of genes involved in nephrogenesis showed clear differences.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It has previously been shown that the expression of both genes is upregulated in RMCs [ 5 ], which corroborates our results. Additionally, our findings are in line with the study by Vokshi et al, which showed clusters of cells harboring an EMT signature in single cell transcriptome analyses of a RMC patient sample as well as an enrichment of EMT and hypoxia in two independently generated RMC cell lines [ 13 ]. Although RMCs and ES show similarities in global methylation, as seen in hierarchical clustering ( Figure 1 B), the methylation of genes involved in nephrogenesis showed clear differences.…”
Section: Resultssupporting
confidence: 92%
“…The hypertonicity and hypoxia within the renal medulla and the location of SMARCB1 at 22q11.2, a known hotspot for de novo deletions and translocations that occur under hypoxic stress, are important factors in the progression of RMCs [ 12 ]. A recent study by Vokshi et al [ 13 ] showed an activation of ferroptosis resistance pathways in RMC cells, which helps to link the RMC oncogenic process to its association with the sickle cell trait. The increased iron concentration in the extracellular space caused by sickled red blood cells (RBCs) leads to selective pressure for ferroptosis resistant cells, which seem to be cells harboring a SMARCB1 loss [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that potential therapies that affect the DNA damage pathway, such as PARP inhibitors, including olaparib and niraparib, ATR inhibitors, and WEE1 inhibitors could all present promising therapies for this nccRCC subtype [90]. Single-cell transcriptomics has also identified potential therapeutic targets in medullary RCC, including novel targetable immune checkpoint receptors TIGIT and CD96, contrasting with low PD1 and CTLA4 expression [91]. Another study evaluated somatic and germline mutations from 116 patients with metastatic nccRCC.…”
Section: Next Generation Sequencing Predictive Biomarkers and Potenti...mentioning
confidence: 98%